(.I_CAN_FLY.)
1 phút trước

2.Sylvia always listens to music.She never watches TV

3.Chris often skates in the park.He sometimes plays computer games

4.Victoria usually goes out with friends.She never stays at home

Bình luận (0)
_silverlining
Vài giây trước

Sylvia always listens to music. She never watches TV
Chris often skates in the park. He sometimes plays computer games
Victoria usually goes out with friends. She never stays at home

Bình luận (0)
Tuệ Lâm Đỗ
3 phút trước

b.

\(=x^2+2xy+y^2-2xy-2xy=\left(x+y\right)^2-4xy=7^2-4.6=49-24=25\)

Bình luận (1)

a, \(\dfrac{2y+2x}{xy}=\dfrac{2\left(x+y\right)}{xy}=\dfrac{14}{6}=\dfrac{7}{3}\)

b, \(\left(x+y\right)^2-4xy=49-24=25\)

c, \(\left(x+y\right)^3-3xy\left(x+y\right)==343-3.6.7=217\)

d, \(\left\{{}\begin{matrix}y=\dfrac{6}{x}\\x+\dfrac{6}{x}=7\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=\dfrac{6}{x}\\x^2+6-7x=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}y=1;y=6\\\left[{}\begin{matrix}x=1\\x=6\end{matrix}\right.\end{matrix}\right.\)

Với x = 1 ; y = 6 thì 

\(\dfrac{1+36}{\left|1-6\right|}=\dfrac{37}{5}\)

Với x = 6 ; y = 1 thì \(\dfrac{36+1}{\left|6-1\right|}=\dfrac{37}{5}\)

Bình luận (0)

mik sẽ biến đổi r bn tự thay số vào nha

a) dễ r bn tự làm nha

b)   \(x^2+y^2-2xy\)

\(=\left(x+y\right)^2-2xy-2xy=\left(x+y\right)^2-4xy\)

c)  \(x^3+y^3\)

\(=\left(x+y\right)\left(x^2-xy+y^2\right)=\left(x+y\right)\left(x^2+y^2-xy\right)\)

d)  \(\dfrac{x^2+y^2}{\left|x-y\right|}\)

\(=\dfrac{\left(x+y\right)^2-2xy}{\sqrt{x-y}^2}\)

\(=\dfrac{\left(x+y\right)^2-2xy}{\sqrt{x^2-2xy+y^2}}\)

\(=\dfrac{\left(x+y\right)^2-2xy}{\sqrt{x^2+y^2-2xy}}\)

Bình luận (0)
Lê Michael
4 phút trước

`(-13 .2/5 +( -2/9) : 5/2 + 2/5 . 11/9) . 5/2`

`=(-13 . 2/5 - 2/9 . 2/5 + 2/5 . 11/9).5/2`

`=[ 2/5 . ( -13 - 2/9 + 11/9).5/2`

`=[2/5. (-12)] . 5/2`

`=(-24)/5 . 5/2`

`= (-24.5)/(5.2)`

`=-120/10`

`=-12`

 

Bình luận (7)
OH-YEAH^^
4 phút trước

\(\left(-13.\dfrac{2}{5}+-\dfrac{2}{9}:\dfrac{5}{2}+\dfrac{2}{5}.\dfrac{11}{9}\right).\dfrac{5}{2}\)

\(=\left[\dfrac{2}{5}\left(-13-\dfrac{2}{9}+\dfrac{11}{9}\right)\right]\dfrac{5}{2}\)

\(=\dfrac{2}{5}.-12.\dfrac{5}{2}=-12\)

 

 

Bình luận (2)
kodo sinichi
3 phút trước

$#flo2k9$

_________________________________________

`(-13 . 2/5 + -2/9 : 5/2 + 2/5 . 11/9) . 5/2`

`= (-13 . 2/5  + -2/9 . 2/5 + 2/5 . 11/9) . 5/2`

`= [(-13 + -2/9 + 11/9) . 2/5) . 5/2`

`= (-12) . 2/5 . 5/2`

`= -12 . 1`

`= -12`

Bình luận (2)
_silverlining
8 phút trước

bài trên thấy làm ròi
You always go to bed at 9 o'clock
We usually go to the cinema on Wednesday
I often read a magazine on Sunday morning
She never eats fish
He always does his homework on Fridays

Bình luận (0)
|{h@notwibu
5 phút trước

2. You always go to bed at 6 o'clock.
3. We usually go to the cinema on Wed.
4. I often read a magazine on Sun morning.
5. She never eats fish.
6. He always does his HW on Fri.
tên ngày mik ziết tắt nha :))

 

 

 

 

Bình luận (0)

a: \(=7^8\)

b: \(=3^{16}\)

c: \(=\left(-6\right)^6=6^6\)

d: \(=\left(-2\right)^{11}\)

e: \(=\left(-0.1\right)^5\)

f: \(=\left(\dfrac{4}{5}\right)^7\)

Bình luận (0)
So_Min_Hwan
5 phút trước

`7^3*7^5=7^{3+5}=7^8`

`3^7*3^9=3^{7+9}=3^16`

`(-6)^5*(-6)=(-6)^6`

`(-2)^5*(-2)^6=(-2)^{5+6}=(-2)^{11}`

`(-0,1)^2*(-0,1)^3=(-0,1)^{2+3}=(-0,1)^6`

Các câu còn lại tương tự nhé

Bình luận (1)

7^3.7^5 = 7^8

3^7.3^9 = 3^16

(-6)^5.(-6) = (-6)^6

(-2)^5.(-2)^6 = (-2)^11

(-0,1)^2.(-0,1)^3 = (-0,1)^5

(4/5)^4.(4/5)^3 = (4/5)^7

(1/2).(1/2)^2 = (1/2)^3

(-1/2).(-1/2)^3 = (-1/2)^4

(-3/2)^3.(-3/2)^2 = (-3/2)^5

(-2).2^8 ( câu này thì tui ko nhớ, sorry )

Bình luận (0)

a: A=-2/5+2/5+3/4-3/4+6/7=6/7

b: A=-1/8-7/8+7/9+6/7+1/7

=7/9

c: A=2/3+2/7=20/21

e: \(=\dfrac{4\cdot13-4\cdot40}{3\cdot9}=\dfrac{4\cdot\left(-27\right)}{-27}=-4\)

Bình luận (1)
Lê Michael
7 phút trước

`A = -2/5 + 3/(-4) + 6/7 + 3/4 + 2/5`

`A=  (-2/5+2/5)+(3/(-4) + 3/4) + 6/7`

`A = 0+0+6/7`

`A=6/7`

________________________

`B=-1/8 + 7/9 + 7/(-8) + 6/7 + 2/14`

`B = (-1/8 + 7/(-8)) + (6/7 + 2/14) + 7/9`

`B = -1 + 1 + 7/9`

`B = 0+ 7/9`

`B  =7/9`

_________________________________________

`A = 2/3 + 1/5 . 10/7`

`A = 2/3 + (1xx10)/(5xx7)`

`A = 2/3 + 57/35`

`A= 241/105`

___________________________

`B = 7/12 - 27/7 . 1/18`

`B = 7/12 - (27.1)/(7.18)`

`B=7/12- 3/14`

`B= 31/84`

__________________________

`4/9 . 13/3 - 4/3 . 40/9`

`=(4.13)/(9.3) - (4.40)/(3.9)`

`=(4.13-4.40)/(9.3)`

`=(4.(13-40))/27`

`=(4.(-27))/27`

`=-4`

____________________________________

`M=1/(3.5) + 1/(5.7) + 1/(7.9) + .... +1/(97.99)`

`M = 1/2 . (2/(3.5) + 2/(5.7) + 2/(7.9) + .... +2/(97.99))`

`M = 1/2 . (1/3 - 1/5 + 1/5 - 1/7 + ...... + 1/97 - 1/99)`

`M = 1/2 . (1/3 - 1/99)`

`M = 1/2 . 32/99`

`M= 16/99`

Bình luận (0)
Đặng Phương Linh
2 phút trước

a/\(A=\left(-\dfrac{2}{5}+\dfrac{2}{5}\right)+\left(\dfrac{3}{-4}+\dfrac{3}{4}\right)+\dfrac{6}{7}=0+0+\dfrac{6}{7}=\dfrac{6}{7}\)

b/ \(B=\left(\dfrac{-1}{8}+\dfrac{7}{-8}\right)+\dfrac{7}{9}+\left(\dfrac{6}{7}+\dfrac{2}{14}\right)=\left(-\dfrac{1}{8}+\dfrac{-7}{8}\right)+\dfrac{7}{9}+\left(\dfrac{6}{7}+\dfrac{1}{7}\right)\\ =-1+\dfrac{7}{9}+1=0+\dfrac{7}{9}=\dfrac{7}{9}\)

c/

\(A=\dfrac{2}{3}+\dfrac{1.10}{5.7}=\dfrac{2}{3}+\dfrac{1.5.2}{5.7}=\dfrac{2}{3}+\dfrac{2}{7}=\dfrac{20}{21}\)

D/

\(B=\dfrac{7}{12}-\dfrac{27.1}{7.18}=\dfrac{7}{12}-\dfrac{9.3.1}{7.2.9}=\dfrac{7}{12}-\dfrac{3}{14}=\dfrac{31}{84}\)

E/

\(=\dfrac{4}{9}.\dfrac{13}{3}-\dfrac{4}{9}.\dfrac{40}{3}=\dfrac{4}{9}.\left(\dfrac{13}{3}-\dfrac{40}{3}\right)=\dfrac{4}{9}.\left(-\dfrac{27}{3}\right)=\dfrac{4}{9}.\left(-9\right)=-4\)

F/

\(\Rightarrow2M=2\left(\dfrac{1}{3.5}+\dfrac{1}{5.7}+...+\dfrac{1}{97.99}\right)\)

\(2M=\dfrac{2}{3.5}+\dfrac{2}{5.7}+...+\dfrac{2}{97.99}\)

\(2M=\dfrac{1}{3}-\dfrac{1}{5}+\dfrac{1}{5}-\dfrac{1}{7}+...+\dfrac{1}{97}-\dfrac{1}{99}\\ 2M=\dfrac{1}{3}-\dfrac{1}{99}=\dfrac{32}{99}\)

\(\Rightarrow M=\dfrac{32}{99}:2=\dfrac{16}{99}\)

 

 

 

 

Bình luận (0)
Lưu Mẫn Nghi
9 phút trước

Áp dụng đl pytago đảo vào tg ABC

Ta thấy : \(BC=\sqrt{AB^2+AC^2}\)

\(50=\sqrt{48^2+14^2}\)

=> tg ABC vuông tại A

=> góc B + góc C = 90o ( phụ nhau )

=> \(sinB=cosC\)

=> góc C = 60o

=> phgiác góc C = 30o

Bình luận (0)